Patient Attitudes Toward Spoken Surveys in a Low-Income Urban Surgical Clinic. Issue 6 (June 2021) - Burgoon, Montgomry L.; Miller, Parker A.; Hoover-Hankerson, Bryson; Strand, Nicolle; Ross, Howard
Diverse groups in urban settings demonstrate poor participation in health care and low levels of literacy. It is possible the method of health information delivery (eg, spoken vs. written) in these settings could impact health care related communication and understanding, though little is known on this topic. The objective of this study was to uncover the advantages and disadvantages of spoken survey administration in a low-income urban setting. The data for this study were collected via spoken survey with eighty patients in 9 surgery clinics at Temple University Hospital (TUH) in North Philadelphia. Survey responses were coded into various groups until categories and relationships among them emerged to produce themes relevant in demonstrating the advantages and disadvantages of spoken survey. 69% (55) of respondents preferred a spoken survey format. Of the 55 patients who preferred the spoken format, 33% (18) possessed some level of college education and 47% (26) had finished high school. Of the 23 patients who primarily spoke Spanish or another language at home, 78% (18) preferred a spoken interview format. Overall, 53% (42) of patients experienced at least 1 instance of poor understanding throughout the survey. Patients were better able to understand questions in a spoken survey compared to written ones that they had completed in the past due to the opportunity for surveyors to explain questions when needed. It is possible that question explanation is necessary in low-income urban settings due to low-literacy levels or improved feelings of survey intimacy and efficiency.